Current Migrations of Bulgarians from Albania to Bulgaria. Towards a New Migration Model of the Historical Bulgarian Diaspora - Tashev, Spas (Research Papers, 2021)
The article reviews the past and current state of the Bulgarian community in Albania. The existing interactions between the Bulgarians in Albania and the Bulgarian state are considered. Based on this, and also on the basis of the existing in the past sustainable model of gurbet (seasonal labour migration for profit or livelihood), the circulating temporary or seasonal labour migration is proposed as an optimal migration model.
Keywords: Bulgarians in Аlbania; Historical Bulgarian community; Circulating migration; Labor market